FIRST REPORT OF LEAF SPOT DISEASE OF CALOTROPIS GIGANTEA CAUSED BY PASSALORA CALOTROPIDIS IN LAHORE, PAKISTAN - I. Mukhtar; I. Khokhar; S. Mushtaq (Journal of Animal and Plant Sciences, 2013)
Aak [Calotropis gigantea (L.) R. Br. ex. Ait.] leaf and stem samples infected by leaf spot were collected during August and September 2011 from Lahore Pakistan . Infected leaf and stem surfaces were covered with circular to irregular blackish spots. Conidiophores 15-50 × 4-6 x µm, arising from substomatal stroma in loose fascicles of 8 -15, pale to light golden yellow, simple, sometimes geniculate near tip, 0-3 transversely septate. Conidia solitary, thin and smooth walled, cylindric to cylindro-obclavate, 0-8 septate, obconic base, subobtuse to bluntly rounded tip, 10-130 × 4-6 µm. Morphological characteristics and pathogenecity test confirmed the identification as Passalora calotropidis . However, this is the first report of P. calotropidis on Calotropis gigantea from Pakistan.
Keywords: leaf spot; Calotropus; Pakistan; Passalora calotropidis